Double level de-rotational osteotomy for femoral and tibial external torsion: Report of two cases - Shuntaro Nejima; Marco Maiotti; Steffen Schröter (Journal of Orthopaedic Reports, 2024)
Background: Double level de-rotational osteotomy is indicated for ‘inwardly pointing knee’, which is caused by increased femoral internal torsion and increased tibial external torsion. This report presents two unusual cases of double level de-rotational osteotomy for other patterns of abnormal torsion. Case reports: Two patients, aged 18 and 16, visited the outpatient clinic of our institute with anterior knee pain and difficulty in walking of one of their knees. Preoperative evaluation of the computed tomography images demonstrated both the femur and tibia were externally rotated approximately 10° from normal value. After double level de-rotational osteotomy consisting of femoral and tibial internal de-rotational osteotomies, their anterior knee pain had resolved and they were able to walk smoothly. Conclusion: Double level de-rotational osteotomy consisting of femoral and tibial internal de-rotational osteotomies can be indicated for increased external torsion of the femur and tibia.